Canadian Civil Engineers Pre-1850: Professionals Before Professionalization - White, Richard (Scientia Canadensis, 2000)
AbstractThis article argues for a thorough re-thinking of the origins of the civil engineering profession in Canada. Working from a variety of sources, the richest being the public works papers in the National Archives of Canada, the author has assembled a list of forty-three men who practised as civil engineers in Canada before the railway boom of the 1850s and for whom biographical details are known. They are overwhelmingly men of the upper middle class who received good academic educations before their professional apprenticeships in engineering. Almost none were tradesmen. The civil engineering profession thus appears of much higher status, and much closer to the other traditional gentlemanly professions of the early nineteenth century, than others have recognized. The author goes on to explore to what extent this first generation of civil engineers might be considered true professionals, and what their existence suggests about the society in which they lived and practised.